2021
DOI: 10.3390/pr9061079
|View full text |Cite
|
Sign up to set email alerts
|

A Modification of Palm Waste Lignocellulosic Materials into Biographite Using Iron and Nickel Catalyst

Abstract: This paper presents an alternative way to maximize the utilization of palm waste by implementing a green approach to modify lignocellulosic materials into a highly crystalline biographite. A bio-graphite structure was successfully synthesized by converting lignocellulosic materials via a simple method using palm kernel shell (PKS) as a carbon precursor. This involved the direct impregnation of a catalyst into raw material followed by a thermal treatment. The structural transformation of the carbon was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 61 publications
2
6
0
Order By: Relevance
“…5b, the peaks represent zeolite and phosphorus at 2θ = 8.8 • and 44.6 • respectively due to the phosphoric acid effect in creating activated carbon from the PKS. Other peaks at 2θ = 21.0 .o , 26.6 • , 50.1 • , 59.9 • and 68.1 • represent the amorphous nature of the activated carbon and is consistent with other studies (Imoisili et al, 2020;Ikubanni et al, 2020;Yeboah et al, 2020, andJabarullah et al, 2021).…”
Section: X-ray Diffraction (Xrd) Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…5b, the peaks represent zeolite and phosphorus at 2θ = 8.8 • and 44.6 • respectively due to the phosphoric acid effect in creating activated carbon from the PKS. Other peaks at 2θ = 21.0 .o , 26.6 • , 50.1 • , 59.9 • and 68.1 • represent the amorphous nature of the activated carbon and is consistent with other studies (Imoisili et al, 2020;Ikubanni et al, 2020;Yeboah et al, 2020, andJabarullah et al, 2021).…”
Section: X-ray Diffraction (Xrd) Analysissupporting
confidence: 92%
“…The use of PKS as a precursor to biographite production is a technology that is still underdeveloped. Catalyst impregnation of PKS-based carbon prior to its heat treatment to achieve highly crystalline graphite was studied by both Jabarullah et al (2021) and Othman et al (2021). The results from their study show that a biographite of high crystallinity and low defects with d 002 spacing of 0.3351 nm was realized.…”
Section: Biographitization and Battery Manufacturementioning
confidence: 99%
“…Higher heat treatment temperatures of up to 1000 •C lead to a higher degree of graphitization. XRD data analysis revealed that all samples showed a 2θ = 26• peak, but the samples prepared using an iron catalyst displayed higher and sharper peaks with a lower ID/IG ratio, indicating higher crystallinity and fewer defects [18] Table 1 shows summary of the effect catalytic graphitization. In conclusion, the reviewed studies have shown that the catalytic graphitization process with different metal catalysts has the potential to produce graphite materials from various carbon sources.…”
Section: The Effect Of Using Metals As a Catalyst For The Graphitizat...mentioning
confidence: 99%
“…The next development of the graphitization catalytic method is the use of a bimetallic catalyst in the graphitization process, sawdust has been successfully graphitized using a Ni-Mo catalyst derived from a solution of NiCl2-(NH4)6Mo7O26 at a temperature of 750 C for 2 hours [8]. Another catalytic graphitization process using biomass as a source of carbon are miscanthus grass with iron and cobalt as a catalyst [17], and palm kernel shell waste as a source of carbon with iron and nickel as a catalyst [18] Various attempts were made by researchers to reduce the graphitization temperature and shorten the graphitization time of biomass as a renewable source carbon using metals as a catalyst. This article, thus, focuses on review the graphitization of biomass using metals as a catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, graphitization is a heat treatment process that heats a carbon precursor at high temperatures to transform the amorphous carbon into crystalline graphite [20]. For synthetic graphite production, natural carbon resources such as coal (bituminous coal [21]), anthracite [22], fossil fuels (lignite [23]) and carbonized and graphitized lignocellulosic materials (Kesambi wood [24], palm waste [25,26], etc.) have been used.…”
Section: Introductionmentioning
confidence: 99%